Persepsi dan Preferensi Masyarakat Kota Bandung terhadap Ruang Publik Stadion Gelora Bandung Lautan Api - Marselly Dwiputri; Sarah Aisha; Rafi Mentari; Nurjannah Hamdani (Lakar: Jurnal Arsitektur, 2023)
The Gedebage Primary Center is planned to answer the problem of population density and activity density in the North Bandung Region as the Primary Center for the City of Bandung, so that the Gedebage Region is designated as the Second Primary Center for the City of Bandung in the Urban Spatial Plan. One of the infrastructures that has been built is Gelora Bandung Lautan Api Stadium. This study aims to determine the perceptions and preferences of the people of Bandung City regarding aspects of space size, security, comfort, and circulation conditions to the research area. The method used in this study is to use a quantitative descriptive method using SPSS software. The benefit of this research is to add information about the perceptions and satisfaction of the people of Bandung City towards the Gelora Bandung Lautan Api Stadium as a sports facility and one of the public space facilities. From the research conducted, the results of the analysis show that in terms of people's perception of the use of space, it is necessary to expand the jogging track and bicycle path because most of the people who come to the sports area are for jogging and cycling activities, coupled with supporting facilities, for commercial activities and recreation.